IgA interaction with the asialoglycoprotein receptor. - Stockert, R J (1982)
IgA present in normal human serum reacts with the hepatic receptor specific for asialoglycoproteins as demonstrated by inhibition of receptor-mediated erythroagglutination. Inhibition is reversibly abolished by the oxidation of the galactose or N-acetylgalactosamine residues of IgA with galactose oxidase. The site of receptor recognition appears to be the O-glycosidically linked oligosaccharides present on the hinge region of the IgAI subtype of IgA. The demonstration of a specific binding, in vitro, of IgA by the hepatic receptor suggests that the uptake of polymeric IgA by the liver in vivo may be mediated by this reaction.